2020
DOI: 10.1002/jsfa.10496
|View full text |Cite
|
Sign up to set email alerts
|

Absorption and distribution of root, fruit, and foliar‐applied 45Ca in ‘Clemenules’ mandarin trees

Abstract: BACKGROUNDThe mechanisms of calcium (Ca) absorption and transport in plants are still poorly understood. This study focused on assessing the absorption and distribution of Ca in different plant organs after root (soil), foliar, or fruit application to 6‐year‐old ‘Clemenules’ mandarin trees, grown in pots, using 45Ca as a tracer.RESULTSThe rate of 45Ca absorption and transportation in plant tissues varied according to the treatment method. The fruit and shoot Ca supply led to a rate of 97% to 98% 45Ca retention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…The study found that only a small percentage, approximately 1%, of the applied calcium was transferred to the fruit. The majority of the Ca remained in the treated tissue [ 44 ]. Therefore, understanding the absorption process is crucial for Ca retention in the treated tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The study found that only a small percentage, approximately 1%, of the applied calcium was transferred to the fruit. The majority of the Ca remained in the treated tissue [ 44 ]. Therefore, understanding the absorption process is crucial for Ca retention in the treated tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Given the limited translocation of Ca from leaves to fruits and within the plant during fruit growth [ 33 , 34 ], the application of Ca sprays to developing fruits is often recommended [ 35 , 36 , 37 ]. The absorption of foliar-applied Ca-carbonate particles may be related to the stomatal pathway when the pores are open [ 38 ], especially if surfactants are added to the foliar treatments [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of the strategies commonly used to improve the concentration of nutrients in the upper plant parts is the application of these nutrients via the foliar route combined with standard root fertilization programs [6]. However, this method is not always applicable for Ca because of its limited transport through the phloem and its minimal distribution towards the growing plant tissues (e.g., fruits) [7,8]. Currently, with vectoring process, it is possible to increase the foliar absorption, the concentration, and the distribution of these elements with low phloem mobility through different plant shoot organs including fruit [9][10][11].…”
Section: Introductionmentioning
confidence: 99%